La diversité des approches comme levier pour favoriser l'accrochage. Étude d'un dispositif pour élèves en rupture - Chantal Tièche Christinat; Valérie Angelucci; Léonie Liechti (Université de Provence, 2016)
By means of focus groups (n=10) and considering the importance of pedagogical components in the process of school dropout, this research aims to understand the activity of professionals involved in a program promoting school engagement on alterning courses (Canton of Vaud, Switzerland). The study examines the nature of pedagogical levers used by the professionals in order to achieve the objective of school engagement. It also focuses on meanings professionals give to the learning situations implemented. Content analysis conducted has yielded three approaches privileged to enhance school engagement, which are operationalized through academic or alternative activities. The substantial weight given to psycho-clinical and socio-educative approaches shows a relative focus on (re)construction of the pupil and his or her socialisation. The emphasis on motivation as a condition rather than the result of learning and academic knowledge relegates the importance of educational and cognitive issues.